Possibilities of networked electronic theses in Japan. Issue 4 (3rd June 2014) - Shuto, Makoto; Manaka, Takayuki; Nakayama, Satoshi; Uchijima, Hideki
Abstract : Purpose: – The purpose of this paper is to investigate/explore the possibilities of nationwide networked electronic theses in Japan. Design/methodology/approach: – The main points of the revised degree regulations, the activities of related organizations corresponding to the revised degree regulations, and the future direction of networked electronic theses which can be realized due to the network of institutional repositories are described and explained. Findings: – In Japan, following the revision of the degree regulations, nationwide electronic thesis networks will be formed, which are rarely observed in other countries, and an infrastructure will be constructed, by which institutional repositories in Japan can be harvested by the Networked Digital Library of Theses and Dissertations. A well-established community of institutional repositories has enabled this achievement to take place. Originality/value: – Very few national laws and regulations oblige a person who has been conferred a doctorate to publicize the thesis through the internet. There are only a few countries where the standard for metadata was established and metadata harvesting using the Open Archives Initiative Protocol for Metadata Harvesting is being performed, providing one-stop services through portal sites. Therefore, this case study on the possibilities of nationwide networked electronic theses attributable to policies and the innovations of the repository network in Japan can provide useful information not only for persons in charge of digitizing dissertations but also for those concerned about open access generally.